A Predictive Study of the Severity of Covid 19 Symptoms According to Neutrosophic Logic (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
The study aimed to use regression analysis as a predictive method for the severity of symptoms of Covid 20 disease according to the classical and Neutrosophic logic in terms of the primary health status of corona patients. To achieve the objectives of the study, a tool was prepared to measure the primary health status of a patient with Covid 20 disease, consisting of (sex, smoking, diabetes, pressure, lung disease, heart disease, thyroid disease, previous malignant disease), and a tool was prepared to measure the severity of symptoms of Covid 20 disease. represented by (loss of the sense of taste, loss of the sense of smell, pharyngitis, fever, cough, difficulty breathing, and diarrhea), and the validity and reliability of these terms were confirmed in measuring each of the patient’s initial health status and the severity of symptoms by applying it to a sample consisting of (1116) Covid-20 disease by the method of internal consistency, Krumbach's alpha stability, and half-segment stability, and both scales showed good validity and reliability indicators.The researcher analyzed the linear regression of the severity of the symptoms of Covid 20 disease in terms of the initial health status by using a linear equation with statistical significance on the complete data after replacing the missing values ​​with the maximum odds method:Then the researcher analyzed the linear regression of the severity of the symptoms of Covid 19 disease in terms of the initial health status, with a linear equation with statistical significance on the complete data after replacing the missing values ​​with the indeterminacy coefficient, as shown by the following relationship